Relationships between climate change, phenology, edaphic factors, and net primary productivity across the Tibetan Plateau - Huaizhang Sun; Yangbo Chen; Junnan Xiong; Chongchong Ye; Zhiwei Yong; Yi Wang; Dong He; Shichao Xu (International Journal of Applied Earth Observations and Geoinformation, 2022)
Net primary productivity (NPP) is an important indicator of ecosystem function and sustainability. It plays an important role in the global carbon cycle, especially in the Tibetan Plateau (TP). Until now, few studies have explored the relationships between climate change, phenology, edaphic factors, and NPP. Quantifying NPP trends and exploring the response mechanisms of NPP to climate change, phenology, and edaphic factors is of great significance to ecosystem maintenance and related policy-making. In this study, the length of the growing season (LOS) was retrieved using the threshold method, which was based on normalized difference vegetation index (NDVI) data. Meanwhile, the Carnegie-Ames-Stanford approach model was adopted to develop an NPP dataset based on multiple datasets across the TP from 2000 to 2020. Then, the availability of NPP and LOS datasets were evaluated. On this basis, this study investigated the spatiotemporal patterns of the NPP, and quantitatively analyzed the response mechanism of NPP to climate change, phenology, and edaphic factors in different ecosystems. According to our results, the estimated NPP and LOS datasets had good usability and robustness. The annual total NPP in the TP experienced a significant upward trend (with Slope of 0.88 gCm-2year−1, R2 = 0.42, P < 0.05). The NPP spatial pattern had a strong spatial heterogeneity from the northwest (<250 gC/m2) to the southeast (>850 gC/m2). In addition, the response mechanism of NPP to climate change, phenology, and edaphic factors indicated that the effects of climate change, phenology, and edaphic factors on NPP varied significantly with different terrestrial ecosystems. Specifically, the availabilities of water and heat mediated NPP by regulating soil moisture variability in the alpine meadow (standardized total effect coefficient (STEC) = 0.58) and alpine steppe (STEC = 0.47), but regulating soil temperature (STEC = 0.29) and LOS (STEC = 0.31) in forest. Our results highlighted that soil properties characteristics of the TP should be considered for combating future climate change.